2020
DOI: 10.5296/jas.v8i2.16380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Non-destructive Method Efficiency of Estimating Nitrogen Content in Jambu Plants Grown in Hydroponic System

Abstract: Jambu is considered a leafy vegetable with expressive relevance in the regions that compose the Brazilian Amazon. However, there are challenges regarding its cultivation, particularly for the nutritional management, since there is little technical information that allows an increase in the efficiency of its production. In this sense, nitrogen (N) gains prominence, since it is related to the increased yield and quality of leafy vegetables, therefore its monitoring of N content in plants is necessary. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…The increase in the number of inflorescences due to the increased application of N in the soil is possibly related to the increase in nutritional demand due to the phenological stage of the plant, especially regarding the reproductive phase, as also observed in vegetables such as lettuce (Martins et al, 2009). Thus, it can be perceived that the growth variables of jambu are responsive to the increased availability of N and the application of limestone in the soil, due to the linear responses obtained, indicating that the plant can still express greater responses in higher concentrations of nutrients in the soil, especially N due to its importance in improving the growth, production and quality of jambu, as already demonstrated in other studies (Borges et al, 2014;Rodrigues et al, 2014;Aviz et al, 2020;Sampaio et al, 2020).…”
Section: Growthsupporting
confidence: 69%
See 1 more Smart Citation
“…The increase in the number of inflorescences due to the increased application of N in the soil is possibly related to the increase in nutritional demand due to the phenological stage of the plant, especially regarding the reproductive phase, as also observed in vegetables such as lettuce (Martins et al, 2009). Thus, it can be perceived that the growth variables of jambu are responsive to the increased availability of N and the application of limestone in the soil, due to the linear responses obtained, indicating that the plant can still express greater responses in higher concentrations of nutrients in the soil, especially N due to its importance in improving the growth, production and quality of jambu, as already demonstrated in other studies (Borges et al, 2014;Rodrigues et al, 2014;Aviz et al, 2020;Sampaio et al, 2020).…”
Section: Growthsupporting
confidence: 69%
“…Similar to the results, Mantovani et al (2005) observed quadratic adjustment for productivity by cultivating different lettuce cultivars as a function of the increase in the N dose, i.e., they observed a reduction in the biomass of the aerial part of the plants from the 176 kg ha -1 dose of N. For jambu, in general, little work is observed regarding the effect of nitrogen fertilization on the productive performance of the crop (Borges et al, 2013;Aviz et al, 2020;Sampaio et al, 2020). Thus, Borges et al (2013) evaluating the effect of nitrogen fertilization on jambu with curral dung and urea, observed that the increase in the dose of these fertilizers in the soil promoted accumulation of fresh and dry mass from the aerial part, highlighting fertilization with urea that obtained better performance.…”
Section: Productionmentioning
confidence: 59%
“…Para Borges et al (2020a) pesquisas em relação a plantas de jambu vem crescendo, devido a necessidades de informações sobre suas ações benéficas a saúde. Apesar de sua grande importância ainda há escassez de informações técnicas acerca do seu cultivo, principalmente quanto suas exigências nutricionais (SAMPAIO et al, 2020), o que torna o processo de adubação quase que empírico.…”
Section: Introductionunclassified